Adenoma of the Ampulla of Vater: A Genetic Condition? - Serafini, Francesco M. (Hindawi Publishing Corporation, 1999)
The etiology of adenoma of the ampulla of Vater is not well understood. Previous authors reported the association of this neoplasm with polycystic kidney disease of two fraternal sisters. They concluded that these two conditions were somehow related. We describe a case of ampullary adenoma associated with polycystic kidney disease. This presentation raises again the question of a possible link between these two diseases.